Healthy families: study protocol for a randomized controlled trial of a screening, brief intervention, and referral to treatment intervention for caregivers to reduce secondhand smoke exposure among pediatric emergency patients - E. Melinda Mahabee-Gittens; Robert T. Ammerman; Jane C. Khoury; Lara Stone; Gabe T. Meyers; John K. Witry; Ashley L. Merianos; Tierney F. Mancuso; Kristin M. W. Stackpole; Berkeley L. Bennett; Laura Akers; Judith S. Gordon (BMC, 2017)
Abstract Background Involuntary exposure to secondhand smoke (SHSe) is an important cause of morbidity in children who present to the pediatric emergency department (PED) and urgent care (UC). SHSe interventions delivered in the PED and UC would benefit both the smoker and child, but there have been no large trials testing the efficacy of such interventions. The Healthy Families program is the first randomized controlled trial to test whether a screening, brief intervention, and referral to treatment (SBIRT) intervention delivered in the PED and UC will be effective in decreasing SHSe in children and increasing cessation in smokers. Methods/design This trial uses a randomized, two-group design in which caregiver-smokers of children 0-17 years old are recruited from the PED and UC. Eligible caregiver-smokers are randomized to either the: 1) SBIRT Condition with face-to-face, tailored counseling that focuses on the child's illness, the importance of reducing child SHSe, caregiver smoking cessation, and the option to receive nicotine replacement therapy; or 2) Healthy Habits Control Condition which includes face-to-face, tailored attention control "5-2-1-0" counseling that focuses on improving the child's health. Dyadic assessments are conducted in-person at baseline, and via email, phone, or in-person at 6-weeks and 6-months. The primary outcomes are biochemically-verified, 7-day point prevalence and prolonged smoking abstinence. Secondary outcomes are cigarettes smoked per week, 24 h quit attempts, and biochemically validated child SHSe at each time point. The costs of this intervention will also be analyzed. Discussion This study will test an innovative, multilevel intervention designed to reduce child SHSe and increase smoking cessation in caregivers. If effective and routinely used, this SBIRT model could reach at least one million smokers a year in the U.S., resulting in significant reductions in caregivers' tobacco use, SHSe-related pediatric illness, and healthcare costs in this population of children. Trial registration ClinicalTrials.gov Identifier: NCT02531594. Date of registration: August 4, 2015.